A Model for Public Relations Management in Islamic Boarding Schools Based on Islamic Values in Addressing Public Stigmatization - Faizatun Fajriah; Eka Diana (Fitrah, 2026)
This study addresses the critical reputational challenges faced by Islamic boarding schools in the digital age, where the rapid flow of information amplifies the risk of public stigmatization. Recognizing their dual role as transmitters of religious knowledge and builders of social legitimacy through communication practices rooted in Islamic values, this study develops a precise model of public relations management for pesantren. The model is grounded in the operationalization of core Islamic values amanah, ṣidq, tablīgh, and ḥikmah and aims to equip Islamic boarding schools with effective strategies to counter negative public perception. Employing a qualitative case study at Pondok Pesantren Kasyifudduja Madura Ra’as, the research demonstrates that integrating religious values with modern public relations practices ensures a more adaptive, ethical, and sustainable institutional reputation. The study’s thesis is that only through such integration can Islamic boarding schools effectively address public stigmatization and maintain credibility in contemporary societal contexts.